2021
DOI: 10.3390/antibiotics10080912
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Continuous Infusion of Vancomycin in Children: A Systematic Review

Abstract: Vancomycin is used to treat a wide variety of infections within the pediatric population. In adults, continuous infusion of vancomycin (CIV) has been evaluated as an alternative to intermittent infusion of vancomycin (IIV) with potential advantages. In children, the use of CIV is increasing; however, data is currently limited. The objective is to provide efficacy and safety evidence for CIV within this population. The review was carried out following PRISMA guidelines. A bibliographic search was performed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(108 reference statements)
1
3
0
Order By: Relevance
“…Literature from both adult and pediatric patients has not shown an increased incidence of nephrotoxicity using CIV. 29 Consistent with these previously published studies, utilization of CIV did not elevate this risk in our patient population. An additional benefit of CIV is the ability to provide additional hydration with the CIV infusion itself, eliminating the need for an additional bag of IV fluids.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Literature from both adult and pediatric patients has not shown an increased incidence of nephrotoxicity using CIV. 29 Consistent with these previously published studies, utilization of CIV did not elevate this risk in our patient population. An additional benefit of CIV is the ability to provide additional hydration with the CIV infusion itself, eliminating the need for an additional bag of IV fluids.…”
Section: Discussionsupporting
confidence: 92%
“…1 These findings are consistent with other recently published institutional cohort studies that also displayed lower TDD associated with continuous administration versus intermittent dosing. [28][29][30] Overall, lower TDD may be beneficial as higher daily doses of vancomycin have been shown to be associated with increased risk of nephrotoxicity. 28 Nephrotoxicity is a significant historical concern when using vancomycin, which requires vigilant monitoring of renal function throughout therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The potential barriers to its implementation might be mainly attributed to the lack of pharmacological knowledge, the absence of an MDT team, and the lack of confidence in clinical practice owing to limited efficacy and safety evidence in pediatrics. Recent published systematic reviews have demonstrated that EI/CI had generally improved clinical outcomes and safety profiles compared with intermittent infusion strategy, with a greater probability of achieving the target ( Costenaro et al, 2020 ; Alonso-Moreno et al, 2021 ; Zhou et al, 2021 ). It is undeniable that the EI/CI strategy has emerged as a promising option ( De Waele et al, 2014 ), even though PK of antibiotics may be affected in critically ill neonates undergoing significant physiological alterations and the appropriateness of EI/CI administration remains further PK/PD or clinical evaluation data ( Wang et al, 2020 ; Saito et al, 2021 ; Yonwises et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As time-dependent antibiotics, extended infusion (EI) or continuous infusion (CI) administration of β-lactams could theoretically lead to improved PK/PD profiles when the concentration remains above the minimum inhibitory concentration (MIC) of the causative pathogen (fT > MIC) for a longer duration ( Rizk et al, 2017 ; Veiga and Paiva, 2018 ). Vancomycin could also theoretically better meet PD targets when provided as prolonged administration ( DiMondi and Rafferty, 2013 ; Gwee et al, 2014 ; Alonso-Moreno et al, 2021 ). Although EI/CI administration for critically ill patients has been suggested by clinical practice guidelines ( Bretonnière et al, 2015 ; Egi et al, 2021 ; Evans et al, 2021 ), there lacks convincing evidence demonstrating its superiority compared with a short-term infusion or bolus dosing in children ( Zhou et al, 2021 ), and pediatricians seem to be not knowledgeable of it or to apply it frequently in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous infusions of vancomycin (CIV) is proposed as one method to achieve the desired AUC 24 /MIC. Continuous infusions of vancomycin delivers the desired serum concentration faster than the IIV method, reduces subtherapeutic episodes, and may decrease drug toxicity (1,4,19).…”
Section: Introductionmentioning
confidence: 99%